SERUM ADIPONECTIN LEVELS IN PATIENTS WITH CORONARY ARTERY DISEASE - Fayyaz, Iram; Ahmed, M. Zamir; Shah, Syed Imran; Mehmood, Sadia; Akram, Shama; Ghani, Mansoor (Journal of Ayub Medical College Abbottabad, 2009)
Background: Adiponectin is an adipocytokine secreted from white adipose tissue. Serum level of adiponectin has been shown to be reduced in several disease states like obesity and diabetes. Hypoadiponectinemia has also been included in the list of newer risk factors for Coronary Artery Disease (CAD). Methods: In this analytical cross-sectional study serum adiponectin level was measured by Enzyme Linked Immunosorbant Assay (ELISA) in 60 cases of coronary artery disease (CAD) (both sexes, aged 40-60 yrs) and 60 healthy controls. Results: Low levels of adiponectin were seen in CAD patients as well as controls. These levels were lower as compared to western standards. Conclusion: Our study conforms to the previous observation of lower serum adiponectin levels in South Asians compared to the western standards. Serum adiponectin level should be considered in the laboratory work-up of CAD patients. Keywords: Coronary Artery Disease (CAD), adiponectin, hypoadiponectinemia, adipocytokine, Enzyme Linked Immunosorbant Assay (ELISA)